2016
DOI: 10.1111/j.1755-3768.2016.0461
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography to distinguish Parkinson disease versus supranuclear progressive palsy

Abstract: PurposeThe aim of the study was to examine patterns of peripapillary andretinal layer damage as a potential marker of neurodegeneration in Parkinson'sdisease (PD) compared to progressive supranuclear palsy (PSP) with 2 SD‐ OCTdevices.MethodsPeripapillary retinal nerve fiber layer (pRNFL), macular thickness (MT)and ganglion cell layer inner plexiform analysis (GCA) by Cirrus and pRNFL analysis and automaticsingle retinal layers macular segmentation by Spectralis were used to evaluate38 patients with PD and 15 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…3). 20 Moreover, macular GCL thickness correlates 132 better with visual dysfunction [visual acuity (VA), low-contrast 133 letter acuity, and vision-specific quality of life measures, 134 visual field mean deviation (MD)], disability and MRI than 135 RNFL thickness. 15,18 136 The improved reproducibility of SD-OCT enhances the 137 value of the analyses use of data from individual quadrants 138 in the longitudinal evaluation of MS patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3). 20 Moreover, macular GCL thickness correlates 132 better with visual dysfunction [visual acuity (VA), low-contrast 133 letter acuity, and vision-specific quality of life measures, 134 visual field mean deviation (MD)], disability and MRI than 135 RNFL thickness. 15,18 136 The improved reproducibility of SD-OCT enhances the 137 value of the analyses use of data from individual quadrants 138 in the longitudinal evaluation of MS patients.…”
mentioning
confidence: 99%
“…Moreover 18 the superior correlation with clinical measures compared to peripapillary retinal nerve fiber layer (pRNFL) suggests that GCL anal-19 ysis might be a better approach to examine MS neurodegeneration. 20 In disorders with optic disk edema, such as ischemic optic neuropathy, papillitis and papilledema, reduction in RNFL thickness 21 caused by axonal atrophy is difficult to distinguish from a swelling resolution. In this setting, and in buried optic nerve head drusen 22 (ONHD), GCL analysis may provide more accurate information than RNFL analysis and it might be an early structural indicator of 23 irreversible neuronal loss.…”
mentioning
confidence: 99%
“…Regarding potential confounding factors among patients' groups, it is noteworthy that patients with a history of ophthalmologic pathologies, including age-related macular degeneration, previous intraocular surgery, glaucomatous optic neuropathy, and diabetic retinopathy, among others, were excluded [9,[20][21][22]24]. When participants' age is concerned, the vast majority of the included studies reported no significant age difference between patients' groups and matched healthy controls; thus, age-related decreases in OCT parameters were not observed [9,19,20,[22][23][24]. In the study by Alkabie et al, it was demonstrated that patients with PSP were significantly older when compared with both the group with PD and control subjects [21].…”
Section: Discussionmentioning
confidence: 99%
“…The first group consisted of three studies focusing on the differentiation between patients with typical (PD) and atypical Parkinsonism (PSP, MSA, and CBS) based on retinal parameters, as assessed with OCT [9,19,20]. The second group comprised three studies investigating the retinal morphology and its potential role in distinguishing patients with PD versus patients with PSP [21][22][23]. Finally, one study explored the value of retinal parameters through OCT in a setting of dementia associated with the presence of Lewy bodies or Parkinson's disease [24] Records identified through the…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation